The integrin αL leg region controls the Mg/EGTA mediated activation of LFA-1 - Guan, Siyu (2015)
We have shown that Mg/EGTA (5 mM Mg(2+) and 1.5 mM EGTA) could effectively promote the adhesion of integrin αLβ2 to its ligand ICAM-1 but could not promote that of the αMβ2 to denatured BSA. In order to determine the structural differences between αL and αM that specifically contribute to Mg/EGTA sensitivity, a series of αL/αM chimeras were constructed. Our results showed that αLβ2 with αM calf-1 domain completely lost the response to Mg/EGTA activation. In the reverse experiment, αMβ2 would require the presence of both the αL calf-1 and calf-2 domain to initiate the Mg/EGTA sensitivity.